Photometry of distant active comet C/2010 S1 (LINEAR) - Shubina, O.; Kulyk, I.; Korsun, P.; Romanjuk, Ya. (Advances in Astronomy and Space Physics, 2014)
We present the results of photometric observations of a dynamically new comet C/2010 S1 (LINEAR), conducted on June 18, 2012. The comet demonstrated a considerable level of physical activity at a heliocentric distance of 6.3 AU. The brightness, measured under a phase angle of 8.9 degrees, was equal to 14.55ᵐ±0.06ᵐ and 14.21ᵐ±0.04ᵐ in V- and R-bands, respectively. The brightness distribution over the coma was found to be inversely proportional to the projected onto the sky plane nucleocentric distance, with a slope of approximately −1. Therefore, the calculated Af ρ parameter, approximately 8400 cm and 8200 cm for V and R filters, respectively, was used to estimate the dust production rate. Assuming a steady outflow of dust particles from the nucleus, the dust production rate was estimated to be between 20 and 60 kg/s, depending on the assumed value of the grain's albedo. The V-R colour index obtained from the near-nucleus region of the coma is in agreement with the solar V-R colour index, and does not indicate significant reddening of the re ected solar radiation in the spectral region of 540-683 nm. Remove selected